Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review: 92

Answer

The solutions are 2 and 3.

Work Step by Step

x(x-5)=-6 x(x-5)+6=-6+6 x(x-5)+6=0 $x^{2}$-5x+6=0 $x^{2}$-2x-3x+6=0 x(x-2)-3(x-2)=0 (x-3)(x-2)=0 x-3=0 or x-2=0 x=3 or x=2 The solutions are 2and 3. Check Let x=2 x(x-5)=-6 2(2-5)=-6 2(-3)=-6 -6=-6 Let x=3 x(x-5)=0-6 3(3-5)=-6 3(-2)=-6 -6=-6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.